Pregnancy and Contraceptive Use Among Women Participating in the FEM-PrEP Trial. (1st February 2015) - Callahan, Rebecca; Nanda, Kavita; Kapiga, Saidi; Malahleha, Mookho; Mandala, Justin; Ogada, Teresa; Van Damme, Lut; Taylor, Douglas
Abstract : Background: Pregnancy among study participants remains a challenge for trials of new HIV prevention agents despite promotion and provision of contraception. We evaluated contraceptive use, pregnancy incidence, and study drug adherence by contraceptive method among women enrolled in the FEM-PrEP trial of once-daily oral tenofovir disoproxil fumarate and emtricitabine (TDF–FTC) for HIV prevention. Methods: We required women to be using effective non-barrier contraception at enrollment. At each monthly follow-up visit, women were counseled on contraceptive use and tested for pregnancy. TDF–FTC adherence was determined by measuring plasma drug concentrations at 4-week intervals. We used Cox proportional hazards models to assess factors associated with incident pregnancy and multivariate logistic regression to examine the relationship between contraceptive method used at enrollment and TDF–FTC adherence. Results: More than half of women were not using effective contraception before enrollment. Ninety-eight percent of these women adopted either injectable (55%) or oral (43%) contraceptives. The overall pregnancy rate was 9.6 per 100 woman-years. Among injectable users and new users of combined oral contraceptives (COCs), the rates were 1.6 and 35.1, respectively. New users of injectables had significantly greater odds of adhering to TDF–FTC than new COC users [odds ratio (95% confidence interval): 4.4 (1.7 to 11.6), P = 0.002], existing COC users [3.1 (1.3 to 7.3), P = 0.01], and existing injectable users [2.4 (1.1 to 5.6), P = 0.04]. Conclusions: Women using COCs during FEM-PrEP, particularly new adopters, were more likely to become pregnant and less likely to adhere to study product than injectable users. HIV prevention trials should consider requiring long-acting methods, including injectables, for study participation.